Psychological impact of online support communities : can human participation in an online health community improve psychological well-being - Kolawole, Olatunbosun (2019)
Online Health Communities (OHCs) have become a major source of social, emotional and informational support for people with health problems. There has been much debate surrounding the potential benefits and costs of online interaction. This debate is centred on the positive and negative effects online health communities have on it users. Social network is believed to have great impact on its participants as suggested by some works of literature, thus participants feel a sense of liberation from any perceived restriction placed in real world either legally, socially or politically. Online Health communities have been able to provide support to these individuals therefore, leading to a positive impact to the individual’s psychological well-being. On the other hand, other line of literature on virtual communities suggest that online social platform can have a negative effect on the participants’ psychological well-being. Therefore, this study focuses on the psychological impact of online health communities. The constructs formulated in this study was based on several construct formulated on studies related to online health communities and psy- chological well-being. The construct utilized to fit the current study includes, social support, social identification, online users behaviour and the psychological flourishing scale. Internet use, education, income level, age and gender were included as control variables. This study result showed that online behaviour, social identification and social support positively impact the psychological well-being of users’ after joining the online health community. While social identification played a positive predominant role in its impact, online behaviour and social support had a considerable positive impact on psychological well-being. Out of five control variables, only age influenced psychological well-being after joining the online community. Overall, the measurement model explained 81% of variance in the impact of online health communities on psychological well-being.